High throughput in silico screening and in vitro testing of polypharmacological bromodomain 4 and cancer associated kinase inhibitors - Phulukdaree, Alisa (University of Pretoria, 2023)
Dissertation (MSc (Physiology))--University of Pretoria, 2022.